Design And Build Scheduling Application Of Production At CV. Gemilang Indonesia - Nahusuly, Nova; Jusak, Jusak; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Gemilang Indonesia (CV. GI) is a company engaged in the field of printing. The production process is currently using machines that work in sequence, starting from the plating machine, a big printing machine, two small printing machines, one machine collator and cutting machines. As such, in the period September 2015 – February 2016 the percentage of delays in processing orders reached 41%. The delays of the production process occurs because the company does not employ any optimization methods for scheduling the machines. For example, there are some products for one order, hence, each product needed to be processed sequentially for each machine. In this case, when the ordered – products are still being processed by the first machine, the orther machines will be idle waiting for the first machine completes the task. To overcome this problems, in this work, we develope an application for scheduling the production in the CV.GI utilizing the First Come First Serve (FCFS), Longest Processing Time (LPT), Shortest Processing Time (SPT), and the Earliest Due Date (EDD). The result of this research is about 94% which means the scheduling production system is feasible to use and can help company in the production schedule.